Predictive value of dynamic changes in RvD1, sST2, and PIV levels for the prognosis of STEMI patients after PCI: a prospective study - Xu, Yiwei; Li, Li; Lin, Zejun; Hu, Yaning; Liu, Yang; Zhou, Tong (Frontiers in Cardiovascular Medicine, 2025)
IntroductionST-segment elevation myocardial infarction (STEMI) is one of the major subtypes of acute coronary syndrome, with rapid progression and a high risk of death and disability. Although some patients undergo timely percutaneous coronary intervention (PCI), they remain at high risk of major adverse cardiovascular events (MACE) after the procedure. In our study, we analyzed the dynamic levels of resolvin D1 (RvD1), soluble suppression of tumorigenicity 2 (sST2) and the pan-immune-inflammation value (PIV) in STEMI patients within 24 h of disease onset and their prognostic value.MethodsThis prospective cohort study enrolled 184 consecutive STEMI patients between December 2023 and December 2024. Serum RvD1 and sST2 levels were measured by enzyme-linked immunosorbent assay at the time of admission (0 h), 6 h post-onset (6 h), and 24 h post-onset (24 h). PIV was derived from routine laboratory data. All patients were followed for 6 months for the occurrence of MACE.ResultsDynamic levels of RvD1, sST2, and PIV differed significantly between patients with and without MACE. Multiple logistic regression analysis confirmed that the sST2 level at admission (OR = 1.056, 95% CI: 1.027–1.086), RvD1 level (OR = 0.234, 95% CI: 0.122–0.449) and LnPIV level (OR = 5.139, 95% CI: 1.743–15.154) at 24 h after onset were strong independent risk factors for MACE (all P < 0.001). With the inclusion of the Global Registry of Acute Coronary Events Study (GRACE) score in the risk prediction model, the area under the curve (AUC) increased to 0.826 (95% CI: 0.758–0.890), 0.852 (95% CI: 0.786–0.932), and 0.834 (95% CI: 0.750–0.897).ConclusionEarly dynamic changes in RvD1, sST2, and PIV are significantly associated with prognosis in STEMI patients. These biomarkers, particularly sST2 level at admission, RvD1 and LnPIV levels at 24 h after onset, serve as independent predictors for MACE and could improve risk stratification.